Complex Analysis of Morphophysiological, Biochemical, and Cytohistological Changes in Peripheral Blood of Patients with Breast Cancer - Jafarova Guzal Alisherovna; Khayitov Davron Gaybullaevich (American Journal of Biomedicine and Pharmacy, 2026)
Breast cancer is one of the most common oncological diseases among women and is characterized by high mortality rates. There is an increasing need for non-invasive, repeatable, and cost-effective diagnostic methods for early detection and prognosis assessment. Peripheral blood serves as a sensitive biological medium reflecting systemic morphophysiological, biochemical, and immunological changes associated with tumor progression. The present study aimed at a comprehensive evaluation of morphophysiological, biochemical, and cytohistological changes in the peripheral blood of patients with breast cancer. The study involved 200 histologically confirmed breast cancer patients (stages I–IV) and 150 healthy control subjects. Hematological, biochemical, and cytohistological parameters were analyzed using modern laboratory techniques and multivariate statistical modeling. The results revealed decreased erythrocyte indices, increased RDW, neutrophilia, lymphopenia, and thrombocytosis in patients. Biochemically, significant increases in CRP, LDH, and oxidative stress markers were observed, which were directly correlated with disease stage. Cytohistological examinations showed erythrocyte anisopoikilocytosis, nuclear atypia of leukocytes, and enhanced lymphocyte apoptosis. These findings indicate that peripheral blood–based biomarkers have high diagnostic and prognostic value.